2020
DOI: 10.1249/mss.0000000000002523
|View full text |Cite
|
Sign up to set email alerts
|

Greater Hamstrings Muscle Hypertrophy but Similar Damage Protection after Training at Long versus Short Muscle Lengths

Abstract: Supplemental digital content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(72 citation statements)
references
References 50 publications
4
66
1
1
Order By: Relevance
“…The increase in bilateral knee flexion 1-RM strength for LL + BFR (11%; 8 kg) is similar to a previous investigation in women (Seo et al, 2016), though was somewhat less than a previous report from our laboratory with a similar population and training protocol (18%; May et al, 2018). This may have been influenced due to differences in knee flexion exercises (i.e., prone knee flexion in the present study vs. seated previously) as the magnitude of hamstrings muscle adaptation appears influenced long muscle lengths (Maeo et al, 2021). Although, knee extension 1-RM strength was also lower than we have previously shown despite similar baseline strength.…”
Section: Muscle Strength and Cross-sectional Areasupporting
confidence: 81%
“…The increase in bilateral knee flexion 1-RM strength for LL + BFR (11%; 8 kg) is similar to a previous investigation in women (Seo et al, 2016), though was somewhat less than a previous report from our laboratory with a similar population and training protocol (18%; May et al, 2018). This may have been influenced due to differences in knee flexion exercises (i.e., prone knee flexion in the present study vs. seated previously) as the magnitude of hamstrings muscle adaptation appears influenced long muscle lengths (Maeo et al, 2021). Although, knee extension 1-RM strength was also lower than we have previously shown despite similar baseline strength.…”
Section: Muscle Strength and Cross-sectional Areasupporting
confidence: 81%
“…A 2018 meta-analysis showed isometric training at longer muscle lengths produced superior increases in muscle size compared to volume-equated training at short muscle lengths. 8 Several studies published subsequent to that paper have shown greater hypertrophy at longer versus shorter muscle lengths in dynamic training of the hamstrings 9 and biceps brachii. 10 Most recently, Pedrosa et al 7 found that pROM knee extension training at a long muscle length was at least as effective, and in some cases superior, in eliciting increases in quadriceps CSA compared to fROM training.…”
Section: Partial Range Of Motion and Muscle Hypertrophy: Not All Roms...mentioning
confidence: 99%
“…This suggests that exercise selection should focus on placing the target muscle in a stretched position. For example, greater hypertrophy has been demonstrated in the hamstrings when performing the seatedversus lying leg curl (159). Similar strategies should therefore be employed to maximize the length-tension relationship when determining exercise selection in program design.…”
Section: Evidence From the Literaturementioning
confidence: 99%